Dual Lactate Clearance in the Viability Assessment of Livers Donated After Circulatory Death With Ex Situ Normothermic Machine Perfusion. Issue 12 (17th November 2021) - Xu, Min; Zhou, Fangyu; Ahmed, Ola; Randle, Lucy V.; Shin, Jun-Kyu; Zhu, Yuehui; Upadhya, Gundumi A.; Byrnes, Kathleen; Wong, Brian; Kim, Jae-Sung; Lin, Yiing; Chapman, William C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Perfusate lactate clearance (LC) is considered one of the useful indicators of liver viability assessment during normothermic machine perfusion (NMP); however, the applicable scope and potential mechanisms of LC remain poorly defined in the setting of liver donation after circulatory death. Methods: The ex situ NMP of end-ischemic human livers was performed using the OrganOx Metra device. We further studied the extracellular signal-regulated kinases (phospho-extracellular signal-regulated kinase1/2 [pERK1/2]) pathway and several clinical parameters of these livers with successful LC (sLC, n = 5) compared with non-sLC (nLC, n = 5) in the perfusate (<2.2 mmol/L at 2 h, n = 5, rapid retrieval without normothermic regional perfusion). Results: We found the pERK1/2 level was substantially higher in the nLC livers than in the sLC livers (n = 5) at 2- and 6-h NMP ( P = 0.035 and P = 0.006, respectively). Immunostaining showed that upregulation of pERK1/2 was in both the hepatocytes and cholangiocytes in the nLC livers. Successful LC was associated with a marginally higher glycogen restoration than nLC at 2 h NMP (n = 5, P = 0.065). Furthermore, bile lactate levels in all sLC livers were cleared into the normal range at 6 h NMP, whereas in the nLC group, only 2 livers had lower bile lactate levels, and the other livers had rising bile lactate levels in comparison with the corresponding perfusate lactate levels. The necrosis scores were higher in the nLC than in the sLC livers (n = 5) at 0- and 6-h NMP ( P = 0.047 and P = 0.053, respectively). Conclusions: The dual LC in perfusate and bile can be helpful in evaluating the hypoxic injury of hepatocytes and cholangiocytes during the NMP of donation after circulatory death in liver donors.